The ‘Letter’ to the Hebrews and Its Thirteenth Chapter - Wedderburn, Alexander J. M. (New Testament studies, 2004)
In addition to the stylistic break at Heb 13.1 which many have noted, the vocabulary and to some extent the content of ch. 13 differ from those of 1–12 and may be more plausibly explained if 13 was written in the knowledge of 1–12 but by a different author and for a different situation.